Interactions of OSW-1 with Lipid Bilayers in Comparison with Digitonin and Soyasaponin - Malabed, Raymond (Langmuir : the ACS journal of surfaces and colloids, 2020)
OSW-1, a unique steroidal saponin isolated from the bulbs of Ornithogalum saundersiae, has potent cell-growth inhibition activity. In this study, we conducted fluorescence measurements and microscopic observations using palmitoyloleoylphosphatidylcholine (POPC)-cholesterol (Chol) bilayers to evaluate the membrane-binding affinity of OSW-1 in comparison with another steroidal saponin, digitonin, and the triterpenoid saponin, soyasaponin Bb(I). The membrane activities of these saponins were evaluated using calcein leakage assays and fitted to the binding isotherm by changing the ratios of saponin-lipids. Digitonin showed the highest binding affinity for the POPC-Chol membrane (Kapp = 0.38 μM-1) and the strongest membrane disruptivity in the bound saponin-lipid ratio at the point of 50% calcein leakage (r50 = 0.47) occurrence. OSW-1 showed slightly lower activity (Kapp = 0.31 μM-1; r50 = 0.78), and the soyasaponin was the lowest in the membrane affinity and the calcein leakage activity (Kapp = 0.017 μM-1; r50 = 1.66). The effect of OSW-1 was further assessed using confocal microscopy in an experiment utilizing DiI and rhodamine 6G as the fluorescence probes. The addition of 30 μM OSW-1 induced inward membrane curvature in some giant unilamellar vesicles (GUVs). At the higher OSW-1 concentration (58 μM, r50 = 0.78) where the 50% calcein leakage was observed, the morphology of some GUVs became elongated. With digitonin at the corresponding concentration (35 μM, r50 = 0.47), membrane disruption and formation of large aggregates in aqueous solution were observed, probably due to a detergent-type mechanism. These saponins, including OSW-1, required Chol to exhibit their potent membrane activity although their mechanisms are thought to be different. At the effective concentration, OSW-1 preferably binds to the bilayers without prominent disruption of vesicles and exerts its activity through the formation of saponin-Chol complexes, probably resulting in membrane permeabilization